(3GHJgGL GdbdhH HNHQ GdTjN CHj GdeMGSf hTjNg GdeLPhHs - (3CHhRjO GdaGSj , YHO GdQMef Hf YHO GdbGOQ Hf Ydj Hf CHj GdeMGSf jhSa GdaGSj,J (B1096 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eSJNdU ef GSJZQb ajg GdCacGQ HeG cTa ef TghO GdChUGa hGdBKGQ s
(3BNQgG (B:s
(3GfJgi ef NWg, hdjcf gPG BNQ eG Yfj HENJUGQg hUdi Gddg Ydi SjOfG eMeO s
(3hGdcJGH oebSe Edi HGHjf hNGJeIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B145s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B694 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B6 s
Keywords: (3GdJGQjNs